2016
DOI: 10.18388/abp.2016_1357
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline and its active metabolite lisofylline attenuate transforming growth factor β1-induced asthmatic bronchial fibroblast-to-myofibroblast transition

Abstract: Bronchial asthma is characterized by persistent airway inflammation and airway wall remodeling. Among many different cells and growth factors triggering changes in bronchi structure, transforming growth factor β1-induced fibroblast to myofibroblast transition is believed to be very important. The aim of this study was to evaluate whether theophylline (used in asthma therapy) and two other methylxanthines (pentoxifylline and its active metabolite lisofylline), may affect transforming growth factor β1-induced fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The majority of drugs currently available for bronchial asthma therapy do not significantly inhibit the fibrotic changes in the bronchial wall [ 29 ]. Only a few anti-inflammatory drugs used in the treatment of asthma (e.g., β 2 -adrenergic receptor agonists, glucocorticosteroids [ 29 ], methylxanthines [ 30 ], and statins [ 17 ]) were suggested to indirectly affect bronchial subepithelial fibrosis. However, numerous studies demonstrated anti-fibrotic effects of fenofibrate in models of hepatic [ 26 , 31 ], cardiac [ 32 , 33 , 34 ], renal [ 35 ], and lung [ 22 ] fibrosis, whereas the impact of fenofibrate on subepithelial fibrosis during asthma progression remains unaddressed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of drugs currently available for bronchial asthma therapy do not significantly inhibit the fibrotic changes in the bronchial wall [ 29 ]. Only a few anti-inflammatory drugs used in the treatment of asthma (e.g., β 2 -adrenergic receptor agonists, glucocorticosteroids [ 29 ], methylxanthines [ 30 ], and statins [ 17 ]) were suggested to indirectly affect bronchial subepithelial fibrosis. However, numerous studies demonstrated anti-fibrotic effects of fenofibrate in models of hepatic [ 26 , 31 ], cardiac [ 32 , 33 , 34 ], renal [ 35 ], and lung [ 22 ] fibrosis, whereas the impact of fenofibrate on subepithelial fibrosis during asthma progression remains unaddressed.…”
Section: Discussionmentioning
confidence: 99%
“…Fenofibrate was already shown to inhibit the TGF-β 1 /Smad signaling axis in fibrotic processes in a model of diabetic nephropathy [ 43 ]. Previously, we showed the impact of statins [ 17 ] and methylxanthines [ 30 ] on the attenuation of the TGF-β 1 /Smad2 signaling axis in HBFs derived from asthma patients. Therefore, a fenofibrate-induced impairment of this signaling pathway may be associated with fenofibrate interference with cholesterol metabolism [ 31 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations